Mendeley Software Training in Improving the Quality of Scientific Articles for Private Higher Education Lecturers - Masduki Asbari; Yunianto Agung Nugroho; Sukriyah; Suroso; Ipang Sasono (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
One of the things that makes a quality written work is related to the element of plagiarism which often occurs as a result of not using a reference manager in citations. In managing references sourced from books or journals, it can be done with the help of several available software/applications, such as Mendeley. Existence software such as Mendeley which can be used to assist with citation writing, allows writers to process their reference documents. Based on the results the implementation of the activity shows that there is an increase in the knowledge and abilities of the participants related to the Mendeley Application before and after the training. However, in terms of the ability to install applications on laptops and Ms. Word as well as using the Application Mendeley to make a bibliography some participants have not been able to master maximum (100%), so it must still be assisted and directed even though the training has been completed implemented. The problem-solving method used is based on the approach management in increasing production and sales results in 3 (three) stages of program implementation, namely preparation, implementation, and evaluation.